Strangers on the Camino : a father, a son-and a holy trail - Wijesinha, Sanjiva (Colombo, Srilanka Vijitha Yapa Publications, 2014)
On pilgrimage to Camino de Santiago de Compostela, also known in English as The Way of St. James,in Spain.
Includes bibliographical references (pages 151-153).
Keywords: Wijesinha, Sanjiva -- Travel -- Spain -- Santiago de Compostela; Christian pilgrims and pilgrimages -- Spain -- Santiago de Compostela; Spain, Northern -- Description and travel; Camino de Santiago de Compostela